Simple and rapid spectrophotometric method for determination of uranium (VI) in low grade uranium ores using arsenazo (III) - Golmohammadi, Hassan; Rashidi, Abbas; Safdari, Seyed Jaber (Publishing House of Lviv Polytechnic National University, 2012)
A simple and highly selective non-extractive spectrophotometric method is presented for the rapid determination of uranium in low grade uranium ores using arsenazo (III). The method is based on the complex formation of uranium (VI) with Arsenazo (III) at pH 2.0 ± 0.1 which showed maximum absorption at 651 m. Uranium concentration of 10 μg g-1 with a molar absorptivity of 4.45×104 mol-1×cm-1 at 296 ± 2 K obeyed Beer’s law. Interferences caused by various metallic ions,such as Mn, Fe, Zn, Mo, Cr, Cu, Co, Ni, Zr, Pb, Al and Na were effectively masked by diethylenetriaminepenta-acetic acid (DTPA) and tartaric acid. The proposed technique has been effectively applied to the determination of low levels of uranium in uranium leach liquors. The accuracy of the current method was checked by comparison with the results obtained by inductively coupled plasma-optical emission spectroscopy (ICP-OES). Приведено простий і високоселективний спектрофотометричний метод для швидкого визначення урану в низькосортних уранових рудах з використанням арсеназо (III). Метод базується на утворенні комплексу урану (VI) з арсеназо (III) за рН = 2,0 ± 0,1 з максимумом поглинання при 651 нм. Концентрації урану порядку 10 мг×г-1 і молярний коефіцієнт поглинання 4,45×104 моль-1×см-1 при 296 ± 2 К підкоряються закону Бера. Вплив різних йонів металів, таких як Mn, Fe, Zn, Mo, Cr, Cu, Co, Ni, Zr, Pb, Al і Na ефективно нейтралізується діетилентриамінопентаоцтовою і винної кислотами. Запропонований метод був ефективно використаний для визначення низьких концентрацій урану в лугах після вилуговування. Точність запропонованого методу була перевірена порівнянням з результатами, отриманими за допомогою індуктивно-зв‘язаної плазмо-оптичної емісійної спектроскопії.
Простий і швидкий спектрофотометричний метод з використанням арсеназо (III) для визначення урану (VI) в низькосортних уранових рудах
Keywords: spectrophotometric method; uranium; arsenazo (III); low grade uranium ores; спектрофотометричний метод; уран; арсеназо (III); низькосортні уранові руди